Quality of life of elderly patients with leg ulcers - Ana Paula Cardoso Tavares; Selma Petra Chaves Sá; Beatriz Guitton R. B. de Oliveira; Ana Inês Sousa (Universidade Federal do Rio de Janeiro, 2017)
Abstract Objectives: To identify compromised domains of the 36-Item Short Form Survey (SF-36) for elderly individuals with leg ulcers and correlate their clinical and sociodemographic variables with the SF-36's components. Method: Exploratory and cross-sectional study conducted with 50 elderly individuals with leg ulcers. The instruments were the sociodemographic and clinical form and the SF-36. The Statistical Package for the Social Sciences was used to analyze data. Results: Most were married, retired, and received one times the minimum wage, were Caucasians or of mixed race, and had hypertension. In regard to the SF-36, the most compromised domain was physical limitations, while social aspects and general health status were the less compromised domains. The SF-36 domains were not correlated with age, income, duration or size of the lesion or pain. Conclusion: The ulcer-related biopsychosocial aspects need to be considered in order to devise more effective nursing interventions.